Book review: Maya Mayblin. Gender, Catholicism, and Morality in Brazil: Virtuous Husbands, Powerful Wives - Ryan Schram (Suomen Antropologi)
MAYBLIN, MAYA. Gender, Catholicism, and Morality in Brazil: Virtuous Husbands, Powerful Wives. New York: Palgrave Macmillan, 2010. Pp. 224. ISBN: 978-0-230-62312-5.